Building Trust, Triggering Skepticism: An ADO–TCM Systematic Review of Green Signaling in Hospitality Marketing - Muneekaew, Pinyapat; Chotisarn, Noptanit; Phuthong, Thadathibesra (International Review of Management and Marketing, 2026)
As hospitality firms increasingly use sustainability signals to attract guests, those signals can both build green trust and trigger skepticism about greenwashing. This review examines how this trust–skepticism dynamic shapes consumer decision-making and addresses the absence of a hospitality-specific synthesis that treats both trust-building and trust-eroding pathways. Following PRISMA 2020, a systematic Scopus search yielded a focused corpus of 18 empirical and conceptual studies, each analyzed through an integrated Antecedents–Decisions–Outcomes (ADO) and Theories–Contexts–Methods (TCM) framework so that findings could be read against the choices that produced them. Three compounding constraints emerge. Research attention is heavily skewed toward trust-building over trust-eroding mechanisms (16:2), leaving their simultaneous operation empirically unmapped; the evidence base relies on a near-monoculture of cross-sectional survey modeling, with cognitive theories of greenwashing absent; and the field is concentrated in a small set of emerging markets. These constraints reinforce one another. The review is, to our knowledge, among the first hospitality green-trust syntheses to integrate ADO and TCM and treats the dual-pathway logic as a single analytical axis. It advances a testable Trust–Skepticism Co-Processing framework and offers guidance to hoteliers, certification bodies, and regulators on how to communicate sustainability credibly while anticipating skepticism.